Precipitation extremes in the Yangtze River Basin, China: Regional frequency and spatial-temporal patterns - Chen, Y.; Zhang, Q.; Xiao, M.; Singh, V.; Leung, Yee-Hong; Jiang, L. (Springer Wien, 2014)
Regional frequency analysis and spatial-temporal patterns of precipitation extremes are investigated based on daily precipitation data covering 1960-2009 using the index-flood L-moments method together with some advanced statistical tests and spatial analysis techniques. The results indicate that: (1) the entire Yangtze River basin can be divided into six homogeneous regions in terms of extreme daily precipitation index. Goodness-of-fit test indicates that Pearson type III (PE3, three parameters), general extreme-value (GEV, three parameters), and general normal (GNO, three parameters) perform well in fitting regional precipitation extremes; (2) the regional growth curves for each homogeneous region with 99 % error bands show that the quantile estimates are reliable enough and can be used when return periods are less than 100 years, and the results indicate that extreme precipitation events are highly probable to occur in regions V and VI, and hence higher risk of floods and droughts; and (3) spatial patterns of annual extreme daily precipitation with return period of 20 years indicate that precipitation amount increases gradually from the upper to the lower Yangtze River basin, showing higher risks of floods and droughts in the middle and lower Yangtze River basin, and this result is in good agreement with those derived from regional growth curves. © 2013 Springer-Verlag Wien.